The effects of coach encouragement on the physical and technical test performances of young tennis players - Barış Karakoç; Yusuf Soylu; Erşan Arslan; Bülent Kilit (Turkish Journal of Kinesiology)
This study investigates the effects of coach encouragement (CE) on the physical and technical performance of young tennis players. Twenty nationally ranked male tennis players (age: 13.6 ± 0.3 years, height: 160.9 ± 7.9 cm, body mass: 52.5 ± 7.6 kg,) participated in the present study. The physical and technical tests were conducted both with and without CE, using a randomized crossover design. Participants attended two sessions for performance assessments, undergoing a series of tests, including the hit and turn tennis test (HTTT), international tennis number test (ITN), counter-movement jump (CMJ) test, 20-m sprint tests, and the T-drill agility test. A paired t-test results demonstrated significant improvements in VO2max, CMJ height, 20-m sprint times, T-drill agility, and ITN scores under CE conditions compared to tests conducted without CE (p < 0.05). These findings suggest that CE positively influences physical and technical performances. Moreover, the effects of CE were more pronounced in long-duration exercises (HTTT and ITN), highlighting the crucial role of motivational support from coaches in the development of young athletes.